2021
DOI: 10.1016/j.ajpc.2021.100223
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Transgender Women Referred to Women's Heart Clinic

Abstract: Introduction Transgender women have been reported to have a high burden of cardiovascular disease (CVD) and risk factors based largely on surveys. Our aim was to describe the prevalence of CVD and associated comorbidities among a cohort of older transgender women referred to cardiology as part of their gender-affirming care. Methods This was a retrospective, cross-sectional study of transgender women at a single institution from 2017 to 2019. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
(51 reference statements)
0
5
0
2
Order By: Relevance
“…La investigación actual sobre comorbilidades cardiacas de las personas transgénero que reciben terapia hormonal cruzada durante el proceso de feminización, es muy limitada debido a los escases de estudios cohortes con un gran número de participantes (12)(13)(14)(15) Contrario a esto, se establece que la edad de inicio es solo un punto de tantos a considerar, para el inicio de la terapia de feminización, ya que se deben tener en cuenta de igual forma, los antecedentes de enfermedades hereditarias que puedan comprometer la homeostasis del organismo una vez iniciado la THC (10). Por su parte, se remarcan la edad y la genética de esta población, como punto de valoración para el inicio de cambio donde determinan que la forma para instaurar esta terapia debe de ser de forma escalonada, a partir de los 16 años hasta la de 18 años de edad, en donde se puede hacer una posterior valoración para la instauración definitive de la THC para este proceso de cambio.…”
Section: Terapia Hormonal Cruzadaunclassified
See 1 more Smart Citation
“…La investigación actual sobre comorbilidades cardiacas de las personas transgénero que reciben terapia hormonal cruzada durante el proceso de feminización, es muy limitada debido a los escases de estudios cohortes con un gran número de participantes (12)(13)(14)(15) Contrario a esto, se establece que la edad de inicio es solo un punto de tantos a considerar, para el inicio de la terapia de feminización, ya que se deben tener en cuenta de igual forma, los antecedentes de enfermedades hereditarias que puedan comprometer la homeostasis del organismo una vez iniciado la THC (10). Por su parte, se remarcan la edad y la genética de esta población, como punto de valoración para el inicio de cambio donde determinan que la forma para instaurar esta terapia debe de ser de forma escalonada, a partir de los 16 años hasta la de 18 años de edad, en donde se puede hacer una posterior valoración para la instauración definitive de la THC para este proceso de cambio.…”
Section: Terapia Hormonal Cruzadaunclassified
“…Para suprimir los caracteres sexuales del sexo biológico, se pueden usar compuestos con efecto anti andrógeno, entre ellos están; la terapia con estrógenos, el cual se puede administrar por tres vías oral (Estradiol), transdérmica (valerato de estradiol) y parenteral (cipionato) (10)(11)(12)(13)(14)(15)(16)(17)(18)(19); La terapia con antiandrógenos, por vía oral (espironolactona, acetato de ciproterona) y transdermica (agonistas de GnRH) (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Además, el seguimiento debe complementarse con exámenes como: Hemograma, niveles de creatinina, ionograma, función hepática, niveles de glucemia y perfil lipídico.…”
Section: Terapia Hormonal Cruzada En La Transición De Masculino a Fem...unclassified
“…To our knowledge, no studies have clearly linked GAHT with changes in coronary calcium or coronary plaque burden. In a small retrospective cohort of transfeminine persons referred for cardiovascular disease testing, 3/7 (43%) presented with detectable coronary calcium with percentile ranges varying from 37% to 88% according to male sex controls and 56% to 97% compared with female sex controls 31. No official guidelines exist as to how radiologists should be applying reference ranges to calcium scoring CT of TGD persons.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…In a small retrospective cohort of transfeminine persons referred for cardiovascular disease testing, 3/7 (43%) presented with detectable coronary calcium with percentile ranges varying from 37% to 88% according to male sex controls and 56% to 97% compared with female sex controls. 31 No official guidelines exist as to how radiologists should be applying reference ranges to calcium scoring CT of TGD persons. Further study is needed to determine the application of sex-based nomograms to determine cardiovascular risks among TGD persons.…”
Section: Masculinizing Hormonesmentioning
confidence: 99%
“…A retrospective cross-sectional study of 52 transgender women referred to a women's cardiology clinic at The Mayo Clinic found that 92% were on GAHT regimens, while the most common reasons for referral were cardiac risk factor management and risk stratification before gender-affirming surgery. 10 As detailed above, much of the current literature has focused on MI rates and changes in biomarkers. However, in comparison to these topics, the effects of GAHT on cardiac mechanics-such as systolic and diastolic dysfunction-are less well-characterized in the literature.…”
mentioning
confidence: 99%